Blue, white and red - Callmer, Johan (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2007)
The production of glass beads from imported glass in Northern Europe, like in other parts of Barbarian Europe, began some time in the Late Roman Period. The local production was on a low technical level and most polychrome beads were imported. Shortly after AD 700 and very suddenly an intensive production of Scandinavian beads, predominantly in blue, white and red glass, commenced. The production was based completely on imported glass in the form of scrap glass, tesserae and various millefiori rods. Several refined production techniques were mastered skilfully. Mastery of the cable technique (reticella) should be noted especially. The bead makers may have been immigrants from the West but to say exactly from where they came is presently impossible. The emergence of this production was probably connected with a relatively small but very creative and active group of artisans. Early on they had split into two groups: one in Eastern and one in South-western Scandinavia. Norway may have constituted a zone of its own. The producers were mobile, working not only at trading sites along the coasts, but also at some inland political centres. About AD 760 the production collapsed completely, possibly as a consequence of some disturbance along the glass supply network and a dramatic reduction in the number of producers. Later, bead production continued, but was based partly on other imported glass, and colours and patterns changed radically. The aesthetics were also different. Imported beads became increasingly numerous, indicating new and more efficient trade routes
ill. ; 24 cm
Keywords: glass beads; bead making technology and chronology; cable technique (reticella); Early Medieval craft production and organization; itinerant craftsmen; cultural values of colour; Early Medieval trade networks